2019
DOI: 10.22146/agritech.12813
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Total Flavonoid of Carica papaya L. Leaves with Different Varieties, Maturity and Solvent

Abstract: Carica papaya leaves are one of the vegetables consumed by Indonesian people, especially in Java Island. Carica papaya is easy to grow in Indonesia and has many variants, so, Carica Papaya leaves is a local potent to be developed for functional food and nutraceutical. The aim of this study was to investigate antioxidant activity and total flavonoids of Carica papaya leaves with different varieties, maturity and solvent. Carica papaya leaves (CPL) was firstly extracted by methanol to select two CPLs with high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
2
11
0
3
Order By: Relevance
“…The highest yield was observed in extraction with 60% ethanol and lowest in distilled water. The result shows some similarity with Fatma et al (2019) which said that, highest flavonoid content is observed in methanol and 70% ethanol whereas lowest in extraction with water. They reported higher content in the mature leaves than in young leaves.…”
Section: Discussionsupporting
confidence: 75%
“…The highest yield was observed in extraction with 60% ethanol and lowest in distilled water. The result shows some similarity with Fatma et al (2019) which said that, highest flavonoid content is observed in methanol and 70% ethanol whereas lowest in extraction with water. They reported higher content in the mature leaves than in young leaves.…”
Section: Discussionsupporting
confidence: 75%
“…of the extract improved liver anatomy with normalization of histopathological damage observed after CCl4 induced hepatotoxicity. Notice that, this hepatoprotective potential might be related to the antioxidant effect played by phenolic compounds [40,6] . Evaluation of the growth inhibitory activity of Carica papaya leaves extract against the tested human cancer cell lines indicates that it inhibits cell growth and stimulates anti-tumor effects.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, bioactive constituents, contents, and biological activities varied between papaya species. Nisa et al [ 17 ] observed that Grendel and purple PL had higher total flavonoid content (50.33 and 46.02 µg/g, respectively) and had a higher percentage of radical scavenging properties than other cultivars such as Bangkok, California, and Golden. In the extract of PLs of the ‘Red Lady’ cultivar, quercetin and its derivatives showed higher antioxidant activity than kaempferol and its derivatives [ 18 ].…”
Section: Introductionmentioning
confidence: 99%